Knowledge of ethnoveterinary medicine in the Province of Granada, Andalusia, Spain. - Benítez, Guillermo; González-Tejero, M. Reyes; Molero-Mesa, Joaquín (Journal of ethnopharmacology, 2012)
This paper constitutes an important contribution to the knowledge of biological resources used in ethnoveterinary practices (EVPs) in southern Europe, a territory with a clear lack of information on the subject. Aim of the study: To catalogue, analyze, and disseminate the knowledge of plant and animal use in eth- noveterinary practices in the province of Granada. Data have been analyzed to highlight the similarities between ethnoveterinary practices and human ethnopharmacology for the same study area. Methodology: Information was gathered through open and semi-structured interviews with local people, mainly elderly shepherds and farmers, in the western part of the province. The primary data have been supplemented with information on EVPs from previous ethnobotanical works for the province. Data were gathered using the same field methods. Results: A total of 88 ethnoveterinary uses are documented for the treatment of 24 animal conditions. Of these, 82 uses involve 60 different plant species. Over three-quarters of these plants are also used for some human conditions in the same study area. Moreover, 6 animal species were catalogued for 6 other ethnoveterinary uses; four of these species were also used for similar conditions in humans. Ritual and health-prevention practices are also discussed. Conclusions: EVPs in southern Spain involve a high number of species and conditions and are strongly linked to folk tradition (i.e. how local people understand certain conditions and their treatment, some- times in a ritual manner). Unfortunately, some evidence of their slow disappearance has been found.
The following values have no corresponding Zotero field: publisher: Elsevier Ireland Ltd accession-num: 22155471
Keywords: Ethnoveterinary; Granada; Spain; Veterinary medicine; Zootherapy

Plant ethnoveterinary practices in two pyrenean territories of catalonia (iberian peninsula) and in two areas of the balearic islands and comparison with ethnobotanical uses in human medicine. - Carrió, Esperança; Rigat, Montse; Garnatje, Teresa; Mayans, Marina; Parada, Montse; Vallès, Joan (Evidence-based complementary and alternative medicine : eCAM, 2012)
This paper presents the results of an ethnobotanical study centred in veterinarian uses in two Catalan Pyrenean regions (Alt Empordà -AE- and High River Ter Valley -AT-, Iberian peninsula) and two Balearic Islands areas (Formentera -FO- and northeastern Mallorca -MA-). In the areas studied, 97 plant species have been claimed to be useful for veterinary purposes. A total of 306 veterinary use reports have been gathered and analysed. The ten most reported plants are Tanacetum parthenium (24 use reports), Parietaria officinalis (15), Ranunculus parnassifolius (14), Meum athamanticum (13), Olea europaea (13), Quercus ilex (12), Ruta chalepensis (12), Sambucus nigra (10) and Thymus vulgaris (10). According to comprehensive reviews, a high number of novelties for plant ethnoveterinary are contributed: 34 species and one subspecies, 11 genera, and three families have not been reported in previous works in this field, and 21 species had only been mentioned once. Several ethnoveterinary uses are coincidental with those in human medicine. Although ethnoveterinary practices are less relevant than in the past in the territories considered, as in all industrialised countries, the knowledge on plant properties and applications is still rich and constitutes a large pool of evidence for phytotherapy, both in domestic animals and humans.
The following values have no corresponding Zotero field: accession-num: 22829861
Keywords: Ethnobotany; medicinal plants (PG); Veterinary medicine

Traditional plant use in the National Park of Cilento and Vallo di Diano, Campania, Southern, Italy. - Di Novella, Riccardo; Di Novella, Nicola; De Martino, Laura; Mancini, Emilia; De Feo, Vincenzo (Journal of ethnopharmacology, 2012)
AIM OF STUDY: This paper reports an ethobotanical survey of the traditional uses of medicinal and useful plants in an area of the National Park of Cilento and Vallo di Diano, Campania, Southern Italy. MATERIALS AND METHODS: This study conducted between 2009 and 2011, gathered information on the medicinal plants traditionally used in Southern Italy (Campania Region). In all, we interviewed 70 key informants, whose age ranged between 50 and 85 years. This people belonged to families which had strong links with traditional activities of the area. RESULTS: The research resulted to the identification of 192 plants belonging to 64 families. Among the species reported, 86 are used in human medicine, 15 in veterinary medicine, 69 as human foods, 18 as animal feed, 61 for domestic and 8 for agricultural uses. CONCLUSION: A survey of the available literature on Southern Italy ethnobotany reveals that some species have been never reported and about 10% of cited uses are new. Data obtained show that in the studied area the folk use of plants is alive and still derives from daily practice.
The following values have no corresponding Zotero field: publisher: Elsevier accession-num: 23159473
Keywords: Agriculture; Agriculture: methods; Animal Feed; Animal Feed: utilization; Data Collection; Ethnobotany; Ethnobotany: methods; Ethnobotany: statistics & numerical data; Ethnomedicine; Food; Humans; Italy; Medicinal; Medicine; National Park of Cilento and Vallo di Diano; plant traditional uses; Plants; Traditional; Traditional: utilization; Veterinary medicine; Veterinary Medicine: methods